Postfeminist, engaged and resistant: Evangelical male clergy attitudes towards gender and women’s ordination in the Church of England - Fry, Alex (Critical research on religion, 2021)
Despite the introduction of female bishops, women do not hold offices on equal terms with men in the Church of England, where conservative evangelical male clergy often reject the validity of women’s ordination. This article explores the gender values of such clergy, investigating how they are expressed and the factors that shape them. Data is drawn from semi-structured interviews and is interpreted with thematic narrative analysis. The themes were analyzed with theories on postfeminism, engaged orthodoxy and group schism. It is argued that participants’ gender values are best understood as postfeminist and that the wider evangelical tradition, as well as a perceived change in Anglican identity with the onset of women’s ordination, shape their postfeminism. Moreover, whilst evangelical gender values possess the potential to foster greater gender equality within the Church of England, gender differentiation limits this possibility, a limitation that could be addressed by increasing participants’ engagement beyond the Church.